2005
DOI: 10.1038/sj.jcbfm.9600016
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Exposure, Mimicked Smoking, Directly and Indirectly Enhanced Protein Kinase C Activity in Isolated Canine Basilar Artery, Resulting in Enhancement of Arterial Contraction

Abstract: Cigarette smoking is a significant risk factor in the incidence of cerebrovascular disorders. Among the many compounds in cigarette smoke, nicotine is considered to most significantly affect cerebral arterial tone. The purpose of this study is to investigate precise pharmacological effects of nicotine on the regulation of cerebral arterial tone. To mimic smoking, a low concentration of nicotine (10 À6 mol/L), which is equivalent to the serum level of habitual smokers, was treated for 1 hour in an isometric ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Nicotine exposure potentiates norepinephrine-induced vasoconstriction in hamster cheek pouch arterioles [46], while the contractility of canine cerebral arteries is increased by nicotine through impairment of endothelial function and activation of PKC activity [47]. Chronic nicotine exposure blunts NO-induced vasodilation [40], suggesting vascular smooth muscle dysfunction as an additional component.…”
Section: Animal Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Nicotine exposure potentiates norepinephrine-induced vasoconstriction in hamster cheek pouch arterioles [46], while the contractility of canine cerebral arteries is increased by nicotine through impairment of endothelial function and activation of PKC activity [47]. Chronic nicotine exposure blunts NO-induced vasodilation [40], suggesting vascular smooth muscle dysfunction as an additional component.…”
Section: Animal Studiesmentioning
confidence: 98%
“…Cigarette smoking causes an upregulation of voltage-gated Ca 2+ channels and a downregulation of Ca 2+ -activated K + (BK) channels in rat cerebral arteries, effects that will attenuate NO-mediated dilation [40]. In canine basilar arteries nicotine potentiates contractile response through PKC activation [47].…”
Section: Cigarette Smokementioning
confidence: 99%
“…11 Koide and colleagues studied canine basilar arterial rings that were exposed to nicotine for 1 hour with endotheliumintact and de-endothelialized samples and no contractile responses were seen on isometric tension studies using uridine triphosphate in either group. 12 They also measured protein kinase C activity, measured substance P-induced vasodilation and NO synthesis, and concluded that nicotine attenuated endothelium-dependent vasodilation by substance P, decreased NO synthesis, and increased protein kinase C activity but that ultimately nicotine does not cause vasoconstriction in canine basilar arteries; however, it may impair endothelial function and enhance protein kinase C activity resulting in an artery prone to vasoconstriction.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Tobacco smoke has been found to increase both blood viscosity and blood volume [23][24][25]. Tobacco smoke also causes vasoconstriction via the inhibition of eNOS and impaired nitric oxide signaling [26][27][28][29]. Therefore, as the viscosity, volume (and flow) increase and as the diameter of the vessel decreases, wall shear stress increases.…”
Section: Pathophysiology Of Tobacco Smoke and Intracranial Aneurysmsmentioning
confidence: 94%